A new search space reduction method based on exergy analysis for distillation columns synthesis. (1st December 2016) - Khalili-Garakani, Amirhossein; Ivakpour, Javad; Kasiri, Norollah
Abstract: In distillation process synthesis as the number of components increased the number of sequences exponentially increased. Besides, there are different categories of sequences which could be considered in the synthesis. So, search space reduction methods are crucial to reduce the number of the candidates and reduce the analysis time. In the present work, a new search space reduction method based on exergy analysis is presented and applied for 3 different samples of three component mixtures (ESI > 1, ESI ≈ 1 & ESI < 1). The feed mixture has been tested under three different compositions. The results of the case study were illustrated that the new method could reduce the amount of calculation between 11 and 50%. Highlights: Presenting an evolutionary synthesis algorithm based on exergy analysis. Developing a new method for reducing the search space and reducing configuration nominees based on exergy loss diagram of distillation columns. Considering thermally coupled, equivalent thermodynamic, divided-wall columns and intensified sequences in the algorithm. Reduction of search space without decreasing the comprehensiveness and precision of the synthesis algorithm. Applying the separation matrix method for generating distillation configurations.